43 State Mental Energy Influences Posture During Vision-Occluded States. (20th December 2019) - Boolani, Ali; Yager, Chelsea; Smith, Matthew Lee; Mondal, Sumona; Sathiyakumar, Thevasha; Senarathna, Dinushani; Teymouri, Seema; Vogel-Rosbrook, Christina; Alvarez, Julieth; Taladay, Phylicia; Martin, Rebecca
Abstract: Background: Fatigue has been postulated to influence postural control, which may lead to an increased risk for falling among older adults. 1 Mental and physical energy and fatigue have recently been reported to be four distinct mood states. 2, 3 Thus, to test Grobe's 1 theory of the influence of fatigue on postural control, we must examine all four mood states. Objective: This study examined the influence of mental and physical energy and fatigue on postural control. Methods: Adults (N=133, Males=50, Females=83, Age=25.8±7.96, BMI=24.8±3.8) aged 18-69 years were recruited from the community and asked to complete a series of surveys that measured their current mental and physical energy and fatigue states. After the completion of the surveys, subjects were instructed to complete the modified Clinical Test of Sensory Interaction in Balance (mCTSIB) using the APDM mobility monitors. Necessary assumptions were verified, and four multivariate multiple regression models were developed. Results: Analyses yielded a significant association between posture and state mental energy (p=.048), but only when subjects were standing with their eyes closed while on a foam surface. Increased feelings of mental energy were associated with decreased total frequency dispersion (b=-358.62) and increased jerk in the coronal plane (b=11.78). No other associations were found. Discussion: Results of our study suggest that as mental energy decreases there is a concomitant decrease in postural control when subjects are placed in conditions where they are unable to rely on visual feedback on unstable surfaces to maintain balance. Progressive increases in postural instability lead to increased risks of falls, most commonly in the elderly population. Falls are a significant risk factor for mortality. This study supports the clinical recommendation either to: (1) improve integration of vestibular and somatosensory input into postural control; or (2) train compensatory strategies for low lighting environments during episodes of decreased mental energy.